Vicious circle [compact disc, unabridged] : a Joe Pickett novel - Box, C. J. (Box, C. J. Joe Pickett novel., 2017)
The Cates family had always been a bad lot. Game warden Joe Pickett had been able to strike a fierce blow against them when the life of his daughter April had been endangered, but he'd always wondered if there'd be a day of reckoning. He's not wondering any longer. Joe knows they're coming after him and his family now. He has his friend Nate by his side, but will that be enough this time? All he can do is prepare; and wait for them to make the first move.